The Effect of Paliative Care Education on The Family Knowledge of Cancer Patients of Bali Branch Rumah Singgah Peduli - Cahyani, Ni Kadek Devi Budi; Suindrayasa, I Made; Utami, Kadek Cahya (Journal of A Sustainable Global South, 2022)
Cancer is one of the biggest killer diseases in the world. Cancer patients have a high need for palliative care. Palliative care is a treatment to improve the quality of life of patients and families in the face of life-threatening diseases. Family knowledge related to palliative care is varies but most families have little information. The purpose of this study was to determine the effect of palliative care education on family knowledge of cancer patients at Bali Branch Rumah Singgah Peduli. This type of research was pre-experimental with the design of one group pre-test post-test design. The study was conducted on April 5 to May 05 2019 with a sample of 36 respondents. The research instrument used was the palliative care knowledge questionnaire and the results were analyzed by the Wilcoxon test. The results of respondents' knowledge scores after the pre-test average were 24.78 and the post-test average score was 33.75. The Wilcoxon test results were p-value 0.000 (p <0.05) showing the influence of palliative care education on cancer patients at the Bali Branch Rumah Singgah Peduli.